﻿Molecular characterisation of three Ixodes (Pholeoixodes) species (Ixodida, Ixodidae) and the first record of Ixodes (Pholeoixodes) kaiseri from Slovakia - Zuzana Krumpálová; Barbara Mangová; Slávka Purgatová; Yuliya M. Didyk; Mária Kazimírová (ZooKeys, 2023)
A study of ticks on wildlife was carried out in the area of Levice, Bratislava, Stupava, and Vrbovce (south-western Slovakia) during 2021 and 2022. Overall, 512 ticks were collected from 51 individuals of six wild mammalian species. Eight tick species were identified, namely Dermacentor reticulatus, D. marginatus, Haemaphysalis inermis, H. concinna, Ixodes ricinus, I. hexagonus, and two Ixodes spp. Ixodes hexagonus were collected from northern white-breasted hedgehogs (Erinaceus roumanicus), females belonging to Ixodes spp. were collected from red fox (Vulpes vulpes) and nymphs from European badger (Meles meles). Ixodes hexagonus and the Ixodes spp. were identified morphologically and molecularly based on sequences of fragments of two mitochondrial genes, COI and 16S rRNA. Molecular analysis of Ixodes spp. confirmed the identity of Ixodes kaiseri Arthur, 1957 and I. canisuga (Johnston, 1849). Sequence analyses show that the I. kaiseri isolate from Slovakia is identical to I. kaiseri isolates from Romania, Poland, Germany, Turkey, and Croatia. We demonstrate for the first time the presence of I. kaiseri in Slovakia using both morphological and molecular methods.